Determining the Dependence of Deformation during Diffusion Welding on the Aspect Ratio Using Samples Made of SS 304 (1.4301). Issue 2 (31st October 2016) - Gietzelt, Thomas; Toth, Volker; Huell, Andreas; Dittmeyer, Roland
Abstract : For uniaxial diffusion welding, deformation depends also on the diameter and height of the parts due to friction between sample and stamp applying the load. Also, the number of surfaces leveled during the welding process affects the deformation: for multilayered parts it is higher than for parts consisting of two halves only. Here, samples of different diameters and heights made of SS 304 are investigated at T = 1 075 °C, p = 25 MPa, and t = 4 h. These values are chosen to achieve reasonable deformation at large diameters and for flat samples as well. A regression is derived to precalculate the deformation. It is verified by experiments for arbitrary diameters and heights. Samples made of sheet material are diffusion‐welded to investigate the influence of the number of layers. Abstract : Experiments show that deformation for diffusion welding with uniaxial pressure depends on aspect ratio and number of bonding planes. For large diameters and small heights deformation decrease. One reason is friction between stamps, possessing a low TEC, and sample. For layered samples, multiple surfaces must be leveled and deformation increase.